ETOS KERJA BANGSA JEPANG DALAM UPAYA PENANGGULANGAN BANJIR - Haryanti, Pitri (Majalah Ilmiah UNIKOM, 2016)
The issue of flood management policies serves polemics in public discourse with no consistency of risk management policies; the arguments continue. As a result, this phenomenon leads to the fact that a technology alone cannot answer the challenges of management risk, and public work projects are promoted to address those challenges. As behavourist’s saying, “mind determines attitude”, one of essential public work projects is related to a change of people’s mind by learning from others’ experienisces. The manipulation of Indonesian’s mind through learning Japanese’s mind is considered as a focus of this research. The research itself aims to examine Japanese indiginious culture to assist Indonesian in identifying and applying its own indigenous culture. Conducting the research, analytic descriptive qualitative approach is applied comprehendly. Analyzing the cases, the research shows that Japanese moral etique, bushido, and its indiginious culture are implemented to formulate flood management policies. Government, private companies, and citizens work together to manage the risk.Keywords : Japanese’s ethos, flood, management policies